2019
DOI: 10.15171/joddd.2019.032
|View full text |Cite
|
Sign up to set email alerts
|

The frequencies of different types of nasal septum deviation and their effect on increasing the thickness of maxillary sinus mucosa

Abstract: Background. Diseases of the paranasal sinuses are very prevalent in East Azerbaijan Province, Iran, which is attributed to various reasons, including environmental and anatomical factors. This study investigated the prevalence of anatomical variations of nasal septum deviation and evaluated the effect of this factor on increasing the mucosal thickness of the sinuses. Methods. The samples included all the patients referred to Tabriz Faculty of Dentistry, and the frequency of nasal septum deviation in the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
2
21
0
2
Order By: Relevance
“…Nasal septum deviation is classified based on the type of shape changes ( Teixeira et al, 2016 ; Taghiloo and Halimi, 2019 ). Some forms of NSD result from uncoordinated growth of the septum and its articulating structures (vomer, ethmoid, nasal bones) resulting frequently in facial asymmetries.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal septum deviation is classified based on the type of shape changes ( Teixeira et al, 2016 ; Taghiloo and Halimi, 2019 ). Some forms of NSD result from uncoordinated growth of the septum and its articulating structures (vomer, ethmoid, nasal bones) resulting frequently in facial asymmetries.…”
Section: Discussionmentioning
confidence: 99%
“…Bayrak et al [ 43 ] reported that there was no correlation between nasal septum deviation and SMT. Meanwhile, Taghiloo and Halimi [ 44 ] investigated changes in SMT based on differences in nasal septum deviation type and showed that there was no difference based on nasal septum deviation type, but increased SMT was observed in 31.76% and 56.67% of males and females with nasal septum deviation, respectively, and there was a significant relationship between nasal septum deviation and thickening of maxillary sinus mucosa. Furthermore, research based on CBCT by Shanbhag et al [ 24 ] showed that ostium obstruction was observed in 13.1% of patients, and that there was a correlation with SMT.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal spur and septal tilt are used to describe localized deviation. Cereke's used the same C and S types as by Guyuron and also included nasal septal deviations [6][7][8]. According to Mladina, septal deformities are of seven types.…”
Section: Classifiation and Clinical Featuresmentioning
confidence: 99%